Use of Poetry in the English as a Second Language Classroom: A Study of Second Year Undergraduates in Sabaragamuwa University of Sri Lanka - Gardihewa, P. N. (Vidyodaya Journal of Humanities and Social Sciences, Faculty of Humanities and Social Sciences, University of Sri Jayewardenepura, 2022)
This study focuses on the effectiveness of the use of literature among English as a Second Language (ESL) students. The purpose of this study is to investigate whether poetry has an impact on language teaching and learning in undergraduates in the English as a second language (ESL) classroom. This study focuses on poetry as a motivation factor and as a productive method to practice language in the ESL classroom. The target population was randomly selected from the second-year students who offer Center for English Language Learning (CELL) as their core subject for their degree program. The students were chosen at random from the sample, with 20 individuals divided into two groups. After the class, the first group was tested using non-literature content, and their scores were recorded. The second group received the identical instruction as the first, with the same test results. As a result, after learning the lesson through a poem, the second group was tested again, and their scores were recorded. They were also given a questionnaire to gauge their degree of satisfaction. The effectiveness of using poetry in learning and teaching was examined by comparing the independent variables. When the effectiveness of the employment of poetry in second language learning students is measured, the outcome-oriented examination shows no difference. There seem certain positive and negative effects.
Keywords: ESL Effectiveness Literature Poetry Undergraduates